Surgical Unroofing for Intramural Aortic Course of Left Main Coronary Artery Leading Reverse Vessel Remodeling. (November 2020) - Akazawa, Yusuke; Chisaka, Toshiyuki; Higaki, Takashi; Uchita, Shunji; Nishiyama, Hikaru; Inaba, Shinji; Moritani, Tomozo; Takata, Hidemi; Yamaguchi, Osamu; Eguchi, Mariko
Abstract : Supplemental Digital Content is available in the text.